A meta-analysis investigating the outcomes and correlation between heart rate variability biofeedback training on depressive symptoms and heart rate variability outcomes versus standard treatment in comorbid adult populations - Donnelly, Daniel; Georgiadis, Emmanouil; Stavrou, Nektarios (Acta Biomedica Atenei Parmensis, 2023)
Background and Aim: Heart rate variability biofeedback (HRVB) has previously been used to ameliorate depressive symptoms but its uses for tackling depressive symptoms in an array of comorbid adult patients is less established. This meta-analysis aims to evaluate whether HRVB is a useful tool to reduce depressive symptoms and improve HRV relative to standard treatment in adult comorbid populations, while also attempting to establish the association between the two outcomes. Methods: An extensive literature review was conducted using several databases including PubMed, Cinahl, Medline, Web of science and clinical.gov/UK register. A total of 149 studies were identified with 9 studies, totalling 428 participants were analysed using a random effects model. Results: Depressive outcomes yielded a mean effect size g=0.478 (CI 95% 0.212, 0.743) with HRV outcomes, yielding a mean effect size of g=0.223 (95% CI 0.036 to 0.411). Total heterogeneity was non-significant for depressive outcomes (Q= 13.77, p=0.088 I^=42.86%) and HRV (Q= 1.598, p=0.991, I^=0.000%) which indicates that little variance existed for the included studies. Conclusions: In summary, the outcomes demonstrate that HRVB can improve both clinically relevant depressive symptoms and physiological HRV outcomes in various comorbid conditions in adult populations, while the correlation between the two was moderately negative, but non-significant.